To simplify the expression, first calculate the fractions inside the parentheses:
(9/7 - 12/7) = (9 - 12)/7 = -3/7
Now, divide this result by 1/6:
(-3/7) / (1/6) = (-3/7) * (6/1) = -18/7
Therefore, the value of the expression is -18/7.
Evaluate the expression shown below and write your answer as a fraction in simplest form.
left bracket, start fraction, 7, divided by, 9, end fraction, minus, start fraction, 7, divided by, 12, end fraction, right bracket, divided by, one sixth
(
9
7
−
12
7
)÷
6
1
1 answer